2023
DOI: 10.3233/wor-211288
|View full text |Cite
|
Sign up to set email alerts
|

Work ability among employees 2–10 years beyond breast cancer diagnosis: Late treatment effects and job resources - A longitudinal study

Abstract: BACKGROUND: The number of workers who have previously undergone a cancer treatment is increasing, and possible late treatment effects (fatigue, physical and cognitive complaints) may affect work ability. OBJECTIVE: The aim of the study was to investigate the impact of late treatment effects and of job resources (autonomy, supportive leadership style, and colleagues’ social support) on the future work ability of employees living 2–10 years beyond a breast cancer diagnosis. METHODS: Data at T1 (baseline question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 64 publications
(103 reference statements)
0
4
0
3
Order By: Relevance
“…Lymphoedema [ 28 ] was not significantly associated with work ability in our study. Treatment induced menopause was associated with reduced work ability in our study, menopause related bodily changes was reported to reduce work ability even in general population [ 38 ], and is described as cause of poor emotional functioning in younger survivors [ 39 ].…”
Section: Discussionmentioning
confidence: 73%
“…Lymphoedema [ 28 ] was not significantly associated with work ability in our study. Treatment induced menopause was associated with reduced work ability in our study, menopause related bodily changes was reported to reduce work ability even in general population [ 38 ], and is described as cause of poor emotional functioning in younger survivors [ 39 ].…”
Section: Discussionmentioning
confidence: 73%
“…Het ging daarbij om betaald werk, maar er waren geen aanvullende eisen aangaande diagnose, behandeling, of het aantal werkuren per week. De minimale (Boelhouwer et al, 2022a(Boelhouwer et al, , 2022b.…”
Section: Methodsunclassified
“…In twee recente studies onder werkenden in loondienst die twee tot tien jaar geleden geconfronteerd werden met borstkanker (Boelhouwer et al, 2022a(Boelhouwer et al, , 2022b, is gebruik gemaakt van het Job Demands-Resources (JD-R) model (Bakker & Demerouti, 2007Demerouti et al, 2001;Schaufeli et al, 2009). Dit model biedt een solide basis voor de onderbouwing van de huidige studie.…”
Section: Theoretisch Kaderunclassified
See 1 more Smart Citation
“…Work ability is a strong predictor of return to work ( 9 ) and a critical factor for successful workplace reintegration in the cancer population ( 10 , 11 ). Work ability in breast cancer patients is lower upon diagnosis ( 12 , 13 ), and although it gradually improves over time ( 13 - 15 ), it remains lower years later ( 16 , 17 ) and compared with cancer-free controls ( 18 , 19 ). Work ability was previously mostly assessed with a single item from the Work Ability Index (WAI) questionnaire, the Work Ability Score (WAS).…”
mentioning
confidence: 99%